IMPLEMENTASI PERATURAN PENATAAN RUANG DI PROVINSI ACEH - Arnita Jamil (Jurnal Transformasi Administrasi, 2021)
Spatial planning is very necessary to realize sustainable development. Sustainable development in Aceh refers to special autonomy. Aceh's Special Autonomy was ratified by Law No. 11 of 2006 concerning Aceh Government. The purpose of Spatial Planning is to regulate, harmonize, harmonize the Planning, Utilization and Control of Spatial Planning. Each region in the State of Indonesia has different interests and needs for the use of space from one region to another. Even the interests of the use of provincial space are not in line with the National Spatial Plan. Therefore, the authors need to discuss how the implementation of spatial planning arrangements in Aceh Province? The implementation of laws and regulations regarding spatial planning starting from laws and regulations to Qanun in Aceh Province cannot be separated from various spatial utilization phenomena. In the implementation of regional autonomy in Aceh, the issue of violation of spatial planning between aspects of spatial planning and the need for space in development for the needs of the community also intersects with each other. Aceh as a special region as well as a region that has special autonomy should apply the principles of spatial planning that are different from other regions in Indonesia. Regional governments, both provincial and district/city governments in Aceh, must be able to realize Aceh's spatial planning arrangements based on Islamic values in accordance with customs, culture, partiality to the poor, community characteristics, and in accordance with Aceh's geographical conditions.